Genotype-phenotype correlations of adult-onset PLA2G6-associated Neurodegeneration: case series and literature review - Yung-Tsai Chu (BMC Neurology, 2020)
Abstract Background Phospholipase A2 group VI (PLA2G6) mutations associated with neurodegeneration (PLAN) manifest as heterogeneous neurodegenerative disorders with variable ages of onset. The genotype-phenotype correlation is not well-established. We aim to describe three adult patients with PLAN and combined these data with results from previous studies to elucidate adult-onset PLA2G6 phenotype-genotype correlations. Case presentations The first index patient presented with dystonia-parkinsonism starting at age 31 years, accompanied by major depression and cognitive decline. Genetic analysis using targeted next generation sequencing (NGS) panel, Sanger sequencing, and segregation analyses revealed a compound heterozygous mutation, c.991G > T (p.D331Y)/c.1077G > A (M358IfsX), in PLA2G6. The other two patients had levodopa-responsive, early-onset parkinsonism, starting in their late twenties. Both patients had homozygous c.991G > T (p.D331Y) mutations in PLA2G6. Patient characteristics of our reported 3 cases were compared to those of 32 previously described (2008 to 2019) patients with adult-onset PLAN. Among the combined cohort of 35 patients with adult-onset PLAN, 14 had dystonia-parkinsonism, 17 had early-onset Parkinson’s disease, 3 had hereditary spastic paraparesis, and one had ataxia. The c.991G > T (p. D331Y) mutation was almost exclusively found in Chinese patients, suggesting a common founder effect. All patients with homozygous p.D331Y mutations had levodopa-responsive, early-onset PD (100%); while other mutations mostly led to dystonia-parkinsonism, ataxia, spasticity, and combine psychiatric comorbidities. Conclusions We showed that adult-onset PLAN could present as purely parkinsonism features, without brain iron accumulation, particularly patients with homozygous p.D331Y mutations. Compound heterozygous mutations, including heterozygous p.D331Y, produced heterogeneous phenotypes, without obvious levodopa responsiveness.